ID: 150. Issue 1 (November 2015) - Neurath, Markus
<x xml:space="preserve">Abstract</x> Cytokines play a crucial role in the pathogenesis of inflammatory bowel diseases (IBD). IBD comprise to different disorders: Crohn's disease and ulcerative colitis. These diseases are characterized by chronic diarrhea, abdominal pain and weight loss and place a significant burden on the affected patients. Cytokines control multiple aspects of the inflammatory response in IBD by binding to their specific cognate receptors on the surface of intestinal target cells. Additionally, cytokines reaching the systemic circulation have been implicated in driving extraintestinal symptoms of IBD (e.g. arthritis). In the inflamed mucosa in IBD, the balance between pro-inflammatory and anti-inflammatory cytokines is altered and pro-inflammatory cytokines dominate the cytokine milieu. This situation impedes the resolution of inflammation and instead leads to disease perpetuation and tissue destruction in IBD. Based on these observations, it is no surprise that anti-cytokine agents have been considered for therapy of IBD. While anti-TNF agents are now used in clinical routine for IBD therapy, other new anti-cytokine agents such as anti-IL12/IL-23 antibodies are on the horizon. Moreover, multi-cytokine blockers such as JAK inhibitors have been recently used in pilot studies for IBD therapy. In this presentation, the role of cytokines in IBD and the current status of anti-cytokine therapy will be reviewed.